Adult Male Rats Show Resilience to Adolescent Bisphenol A Effects on Hormonal and Behavioral Responses While Co-Exposure With Hop Extracts Supports Synergistic Actions - Morin, Alexandre; Van de Beeck, Lise; Person, Emmanuelle; Plamondon, Helene (Frontiers in Toxicology, 2021)
The adolescence period, marked by sexual and brain maturation, has shown sensitivity to various environmental disruptors. Exposure to the xenoestrogen bisphenol A (BPA) is known to alter physiological and behavioral responses although its role at this critical period remains largely unknown. Recent research further suggests biochemical and genomic effects of BPA to be mitigated by various natural compounds, while effects on behavior have not been examined. This study aimed to characterize (1) the effects of dietary BPA during adolescence on endogenous corticosterone (CORT) secretion, emotional behavior, and testosterone (T) in adulthood, and (2) the impact of combined exposure to BPA with hop extracts (Hop), a phytoestrogen with anxiolytic properties. To do so, four groups of male Wistar rats [postnatal day (PND) 28] were administered corn oil (control), BPA (40 mg/kg), hops (40 mg/kg), or BPA-hops by oral gavage for 21 days (PND 28–48). Blood droplets collected on PND 28, 48, and 71 served to measure CORT and T changes. As adults, rats were tested in the elevated plus maze (EPM), the social interaction test, and the forced swim test. Our findings demonstrated elevated anxiety and a trend toward depressive-like behaviors in BPA- compared to hops-exposed rats. However, BPA intake had no impact on basal CORT levels, or adulthood T secretion and sociability. Of note, BPA's anxiogenic effect manifested through decreased EPM open arm entries was abolished by hops co-supplementation. Together, our observations suggest the adolescence period to be less sensitive to deleterious effects of BPA than what has been reported upon gestational and perinatal exposure.